Respuesta :

caylus
Hello,

x²-6x-16=x²+2x-8x-16=x(x+2)-8(x+2)=(x+2)(x-8)

Answer D.

Answer:

Option D is correct

factored form of the given equation is; (x+2)(x-8)

Explanation:

The given quadratic equation is : [tex]x^2-6x-16[/tex]

Now, to convert this quadratic equation into factored form;

[tex]x^2+bx+c =(x+r)(x+s)= x^2+(r+s)x+r\cdot s[/tex]

So, r and s must satisfy:


r+s=b

rs =c

Now, we are looking for a pair of numbers whose product is -16 such as (4,−4), (1, -16), (2, -8). They also have to add up to  -6.

The only choice that satisfies both is (2 , -8).

then;

[tex]x^2-6x-16[/tex] = [tex]x^2-8x+2x-16[/tex]

or

[tex]x^2-8x+2x-16[/tex] = [tex]x(x-8)+2(x-8)[/tex]

Now taking (x-8)  common we get;

[tex]x(x-8)+2(x-8)[/tex] = [tex](x+2)(x-8)[/tex]

therefore, the factored form of the [tex]x^2-6x-16[/tex] is;  [tex](x+2)(x-8)[/tex]